Race, Criminal Records, and Certificates of Relief: An Experimental Pilot Study. Issue 9 (1st September 2020) - Leasure, Peter; Andersen, Tia Stevens
ABSTRACT: In recognition of the importance of securing employment for successful reentry, several states have introduced certificates of relief, which are intended to aid ex-offenders in their job search by demonstrating rehabilitation to potential employers. However, no study has examined potential racial differences in the efficacy of such certificates. Using an experimental correspondence approach, the authors demonstrate that White applicants with certificates of relief received significantly more callbacks for interviews than African American applicants with certificates. Differences between White and African American applicants with criminal records and no certificate and those with no criminal record did not reach statistical significance.